2006
DOI: 10.1007/s00213-006-0433-0
|View full text |Cite
|
Sign up to set email alerts
|

A model for antipsychotic-induced obesity in the male rat

Abstract: This study shows that a rat model of obesity induced by antipsychotics can be created under specific conditions of drug administration, diet, and dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…Consistent with previous studies, olanzapine caused significant metabolic dysregulation, 22,24,31,[37][38][39][40][41][42][43] evident as elevated fasting glucose levels, insulin resistance (greater HOMA-IR values) and glucose intolerance in the IGTT. To our knowledge, we assessed the effects of metformin, rosiglitazone and glyburide on these metabolic side effects in rats for the first time.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, olanzapine caused significant metabolic dysregulation, 22,24,31,[37][38][39][40][41][42][43] evident as elevated fasting glucose levels, insulin resistance (greater HOMA-IR values) and glucose intolerance in the IGTT. To our knowledge, we assessed the effects of metformin, rosiglitazone and glyburide on these metabolic side effects in rats for the first time.…”
Section: Discussionsupporting
confidence: 90%
“…One method to identify a clinical approach toward a weight management strategy is to better understand how SGAs might affect CNS feeding circuitry. Antipsychotic drugassociated weight gain in a male rodent model has been shown by Minet-Ringuet et al (2006); however, clozapine has not been found to induce weight gain or metabolic abnormalities in female rats, but was found to increase adiposity (Cooper et al, 2007). Although antipsychotic drugassociated weight gain in rodent models is in dispute in regard to sex, drug administration, diet, dose, and antipsychotic agents used, the use of OLZ in female rats has consistently been demonstrated to reproduce the weight gain, increased adiposity, and metabolic disturbances seen in patients (Albaugh et al, 2006;Arjona et al, 2004;Coccurello et al, 2006;Cooper et al, 2005;Cope et al, 2005;Goudie et al, 2002;Raskind et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm previous observations of an increased fat deposition in rats under olanzapine treatment. 20,30 And they shed more light on the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…Food intake increased in olanzapinetreated animals without reaching significance (data not shown); the increase in food intake was parallel to the increase in body weight, similar to the results reported in our previously published experiments using the same technique. 20 Lipolytic and antilipolytic activities in adipocytes from control and antipsychotic-treated rats Basal lipolysis was unmodified in adipocytes isolated from the INWAT of antipsychotic-treated rats when compared to control. However, the dose-dependent stimulation of lipolysis induced by the b-adrenergic agonist isoprenaline was significantly weaker in the olanzapine-treated group than in the control group (Figure 2).…”
Section: Adiposity At the End Of Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation